2013
DOI: 10.1177/0956462413486454
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of HIV-infected intravenous drug users

Abstract: To investigate health-related quality of life in HIV-infected intravenous drug users registered but not engaged in HIV outpatient care (missing ≥2 outpatient appointments over 1 year or non-attendance for ≥6 months) we conducted a cross-sectional study to examine health-related quality of life of HIV-infected intravenous drug users registered for care at an inner city HIV unit. EQ-5D, SF-36, SF-6D, mood disorder, clinical and substance misuse data were collected. Mean scores and preference derived utility scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Other international studies have found similar results. Among 55 HIV+ intravenous drug using participants living in Ireland, anxiety predicted lower quality of life irrespective of physical health (Surah et al, 2013). In another study, Hasanah et al (2011) cross-sectionally examined the association of anxiety symptoms on QuoL among 271 HIV infected adults in Malaysia.…”
Section: Anxiety and Its Disorders In Relation To Hiv/aids Clinicamentioning
confidence: 99%
“…Other international studies have found similar results. Among 55 HIV+ intravenous drug using participants living in Ireland, anxiety predicted lower quality of life irrespective of physical health (Surah et al, 2013). In another study, Hasanah et al (2011) cross-sectionally examined the association of anxiety symptoms on QuoL among 271 HIV infected adults in Malaysia.…”
Section: Anxiety and Its Disorders In Relation To Hiv/aids Clinicamentioning
confidence: 99%
“…Compared to patients with HIV/AIDS alone, HIV/AIDS patients with substance use disorders 1618 and other psychiatric disorders 1921 report diminished quality of life. Little research has investigated quality of life in triply diagnosed patients, i.e., those with HIV/AIDS, substance use disorders, and other psychiatric disorders.…”
Section: Introductionmentioning
confidence: 96%
“…When compared to individuals with other chronic diseases, persons living with HIV (PLHIV) have poorer physical functioning and emotional wellbeing (4). Illicit drug use (8, 9), psychiatric conditions (10–12), limited social support (11, 1315), presence of HIV-related symptoms (4, 7, 13), and poor socioeconomic status (16, 17), worsen HRQoL when they co-exist with HIV infection. HRQoL is a known predictor of survival among HIV infected individuals (18).…”
Section: Introductionmentioning
confidence: 99%